PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN YANG BERDAMPAK PADA MINAT BELI ULANG SEBAGAI VARIABEL INTERVEING PADA UD LANCAR JAYA DI KABUPATEN SITUBONDO - Aunillah, Indy Husni; Ediyanto, Ediyanto; Soeliha, Siti (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Marketing is an important part of company management and also a very important factor, because marketing directly affects the company’s success in achieving its goals. It is important for companies to know the right and appropriate marketing strategy for the products to be sold in the market. The purpose of this study was to analyze and test the effect of Product quality in determining Repurchase interest with Consumer satisfaction as an intervening variable. The population in this study are UD Lancar jaya consumers in Situbondo District. Sampling method was determined by simple random sampling. Data analysis and hypothesis testing in this study using the structural equation model – partial least square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Product quality has a significant positive effect on Consumer satisfaction, Product quality has a positive but not significant effect on Repurchase intention, Consumer satisfaction has a significant positive effect on Repurchase interest, Product quality on Repurchase interest through Customer satisfaction has asignificant positive effect.